Study on the Reconstruction of the Spectral Pattern of Near-Island Reef Bimodal Waves - Weihang Sun; Yuguo Pei; Leilei Qu; Xiaobo Wang (Journal of Marine Science and Engineering, 2025)
Accurately fitting bimodal wave spectra is crucial for understanding complex ocean conditions and promoting ocean-related research. In this context, this paper aims to solve the problem of reconstructing bimodal wave spectra in domestic island and reef areas. Taking measured data from the Jiangsu Xiangshui station in August 2017 and the Xisha Sea area on 1–3 August 2014 as case studies, the researchers selected three types of original bimodal wave spectra. After obtaining the sample spectra through fast Fourier transform and wave spectrum non-dimensionalization, this paper selected a novel wave spectrum—the rational fractional unimodal spectrum—and two classical wave spectra—the Jonswap spectrum and the Neumann spectrum. Three bimodal wave spectra were constructed by superimposing the low-frequency sub-spectrum and the high-frequency sub-spectrum. After using the improved PSO algorithm to optimize the parameters of these three bimodal wave spectra, the specific parameters were obtained. Comparisons were made between the above three bimodal wave spectra and three high-precision double-peak fitting spectra, the Huang Peiji six-parameter spectrum, the Ochi-Hubble spectrum, and the Shen Zhichun fitting spectrum, and the fitting effects were analyzed. The results demonstrated that when fitting the bimodal spectrum dominated by wind waves and the bimodal spectrum with comparable wind and swell energy, the combination of the rational fractional unimodal spectrum and the Neumann spectrum can achieve a fitting accuracy of up to 99%. When fitting the bimodal spectrum dominated by swell waves, the combination of the rational fractional unimodal spectrum and the Jonswap spectrum can also achieve a fitting accuracy of 99%. The findings of this paper provide valuable references for the study of other types of double-peak wave spectra in China.